Extraction Optimization of Natural Dye from Clitoria Ternatea Flower by OFAT - Tengku Khamanur Azma, Tg. Mohd Zamri; Mimi Sakinah, A. M.; Zularisam, A. W. (2016)
Dyes are widely used in industries such as textiles, leather, paper, and plastics to colour their final products. This paper highlights an on-going study which the scope is to optimize the extraction of natural dyes from the natural sources. The objective of this study is to determine the optimum conditions of extraction natural dye where the parameters for extraction of natural dye are temperature, solid liquid ratio and time with one factor at one time (OFAT) by utilizing Design Expert V8.0.6. In this research, Clitoria Ternatea flower will be used as the source of natural dyes. The pigment that is contained in Clitoria Ternatea flower called delphinidine. The objective of OFAT was to study the effect reaction of extraction on the Clitoria Ternatea flowers were temperature, time and solid liquid ratio. The extraction temperature at 60 °C contributed to the maximum adsorption of delphinidine. The absorption of delphinidine was higher at time 20minutes and then it reached while the absorbance was increased until solid liquid ratio 1:10